The Effectiveness of the Kumon Learning Strategy in Enhancing Qur’anic Memorization among Kindergarten Children: A Study from an Educational Management Perspective - Soibatul Aslamiah Nasution; Charles; Fadhli Zulmi; Yulda Dina Septiana (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of the Kumon learning strategy in Tahfiz learning at the kindergarten level, with a focus on its effectiveness in improving children’s Qur’anic memorization and the role of educational management in supporting the learning process. Specifically, the study examines the dimensions of planning, implementation, evaluation, and collaboration between teachers and parents in managing Tahfiz learning activities. This research employs a library research method by analyzing relevant literature related to the Kumon method, early childhood education, Tahfiz learning, and educational management. The findings indicate that the application of the Kumon learning strategy positively contributes to increasing children’s learning independence, enhancing the effectiveness of repetition, and improving learning motivation in Qur’anic memorization. From an educational management perspective, effective instructional planning, systematic implementation, continuous evaluation, and strong teacher–parent collaboration are key factors in optimizing learning outcomes. The study implies that the Kumon method can serve as an alternative and innovative instructional strategy in early childhood Tahfiz education, strengthening learning management practices and fostering a harmonious partnership between schools and families to support children’s holistic learning success.